Nonlinear analysis of cracked plates - Purbolaksono J.; Dirgantara T.; Aliabadi M.H. (Trans Tech Publications Ltd, 2023)
This paper presents the geometrically nonlinear analysis of cracked plates by the dual boundary element method. Extrapolation of displacements on the crack surfaces is used to compute the stress intensity factors. The normalized stress intensity factors for the cracked square plate with fully clamped and simply supported boundary conditions are presented.